Empowering Sustainable Startups in Kenya Through Blockchain Technology - Hamba, Loyce Aoko; Odoyo, Wilfred Onyango; Kangethe, Brian Muchiri (LPPM STIKI Malang, 2024)
This study investigates the potential applications of blockchain technology to offer a solid basis for supporting long-term, sustainable Kenyan entrepreneurs. The study investigates how blockchain technology's decentralized, transparent, and secure features might increase investor confidence, increase stakeholder engagement, and speed up funding processes for sustainable projects. The key findings indicate that blockchain can significantly improve transparency, reduce inefficiencies in the fundraising process, and attract a diverse range of investors to support companies. However, barriers including ambiguous laws, complex technology, and poor awareness make widespread adoption challenging. To solve problems, the paper emphasizes the need for an all-encompassing framework that includes capacity building, policy alignment, and clever public-private partnerships. By prioritizing these initiatives, stakeholders may unlock blockchain's transformative potential to assist Kenya's green development goals, foster innovation, and accelerate sustainable startup growth.